(untitled) (Colombia Medica, 2018)
Objective: To analyze the environmental factors (nutritional status, levels of physical activity and nutritional habits) and their possible association with bone mass in a population of young adults. Methods: The study population consisted of 200 subjects (117 women and 83 men) aged between 18 and 25 years (mean age 20.4 years ±2.2 years). Body composition parameters were measured by an electronic balance (TANITA BC-418MA), nutritional habits were estimated by 72-h dietary recall, level of physical activity was assessed by the International Physical Activity Questionnaire (IPAQ) and bone mass was measured by ultrasonography at the calcaneus. Results: There were significant differences in bone mass values according to gender (p= 0.013). Despite the fact that 70% of the subjects had a body mass index (BMI) within the normal range, 20% had overweight or obesity. 49% of the individuals had a moderate level of physical activity, although women had lower levels of physical activity than men (17.9% vs 8.4%). Most diets among young adults were hyperprotic, hyperlipidic and low-carbohydrates, with low-calcium and fiber intakes and high-phosphorus. Analysis of bone mass according to BMI showed higher values as the weight category rises, with significant differences in women. Higher values of bone mass were shown as the level of physical activity was higher, showing significant differences in males. Conclusion: Our results show that BMI and level of physical activity are significantly associated with bone health in a population of young adults, suggesting the relevance of promoting healthy lifestyles as a strategy for the early prevention of osteoporosis.